1965
DOI: 10.1111/j.1365-2672.1965.tb02169.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Recovery Medium on the Isolation of Staphylococcus aureus after Heat Treatment and after the Storage of Frozen or Dried Cells

Abstract: S n n a~m y . The recovery of heated or dried cells of Staphylococcus aureue waa beat on media containing blood or sodium pyruvate. It is suggested that the catalw Recovery of staphylococci 39'a multiple antibiotic resistant strain of phage type 83A; strain E (S 6), used for the production of purified enterotoxin B, and strain F (223), a phage type 42D organism bolsted from a case of bovine mastitis. Inocula were prepared by growing the strains on a shaker for 24 h at 37" in 200 ml amounts of a peptone-yeast e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
1
3

Year Published

1980
1980
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 37 publications
2
42
1
3
Order By: Relevance
“…It has been suggested that fish are often contaminated with S. aureus in this state. Sodium pyruvate has been reported to recover VBNC cells with damaged metabolic pathways [1]. Introducing an enrichment culture method remarkably increased the S. aureus detection rate in agar (Table 2), which is consistent with previous reports [32,33,38].…”
Section: Discussionsupporting
confidence: 82%
“…It has been suggested that fish are often contaminated with S. aureus in this state. Sodium pyruvate has been reported to recover VBNC cells with damaged metabolic pathways [1]. Introducing an enrichment culture method remarkably increased the S. aureus detection rate in agar (Table 2), which is consistent with previous reports [32,33,38].…”
Section: Discussionsupporting
confidence: 82%
“…Most note increased sensitivity to salt and pH following stress from sub lethal heating, drying or storage. Baird-Parker & Davenport (1965) noted that recovery of stressed cells was best on media which supply catalase or otherwise neutralize peroxides. However, in our experiments, catalase deficiency alone would not appear to be the cause of low recovery as both blood agar and BPA contain agents to neutralize effects of peroxides.…”
Section: Discussionmentioning
confidence: 99%
“…Reconstitution of frozen stocks was done by streaking the cultures onto BHI or LB agar followed by incubation at 37°C. Recovery of survivors following stress treatments was carried out on tryptic soy agar supplemented with 0.6% yeast extract (TSA-YE) and 1% sodium pyruvate (4,11). Survival studies for oxidative stress, acid stress, tolerance to ethanol, and osmotic stress were performed in BHI broth augmented according to the methods listed below.…”
Section: Methodsmentioning
confidence: 99%